Association between cardiometabolic index and bone mineral density among adolescents in the United States - Liu, Haobiao; Xiang, Rongqi; Liu, Chenyue; Chen, Zhuohang; Shi, Yuhang; Liu, Yiting; Liu, Yan (Frontiers in Endocrinology, 2025)
ObjectivesThe cardiometabolic index (CMI) serves as a comprehensive metric for evaluating cardiometabolic health, and is correlated with several health outcomes. However, research examining the relationship between CMI and bone mineral density (BMD), particularly in adolescent populations, remains limited and warrants further investigation.MethodsThe weighted multiple linear regression analysis was conducted to elucidate the association between CMI and BMD.ResultsOur study ultimately included 1,514 participants. After adjusting for pertinent covariates, we observed that per-unit increases in the CMI corresponded with reductions in BMD by 0.052 g/cm2 for femoral neck (β=-0.052, 95% CI: -0.087 to -0.018) and 0.048 g/cm2 for lumbar spine (L1-L4) (β=-0.048, 95% CI: -0.085 to -0.011). In quartile analyses, individuals in the highest quartile displayed significantly reduced BMD at the femoral neck (β=-0.036, 95% CI: -0.064 to -0.007) and lumbar spine (L1-L4) (β=-0.041, 95% CI: -0.070 to -0.011) compared to those in the lowest quartile (P<0.05). No statistical significance was detected between CMI and BMD at the total femur, trochanter, and intertrochanter sites. Furthermore, stratified analyses indicated no significant interactions involving age, sex, or race in relation to CMI and BMD.ConclusionsIn the adolescent population, CMI is inversely related to BMD. These findings highlight a potential link between cardiometabolic health and bone health. Future longitudinal investigations are warranted to determine causal relationships and underlying mechanisms.